EULAR recommendations for the management of large vessel vasculitis. Issue 3 (15th April 2008) - Mukhtyar, C; Guillevin, L; Cid, M C; Dasgupta, B; de Groot, K; Gross, W; Hauser, T; Hellmich, B; Jayne, D; Kallenberg, C G M; Merkel, P A; Raspe, H; et al.
Abstract : Objectives: To develop European League Against Rheumatism (EULAR) recommendations for the management of large vessel vasculitis. Methods: An expert group (10 rheumatologists, 3 nephrologists, 2 immunolgists, 2 internists representing 8 European countries and the USA, a clinical epidemiologist and a representative from a drug regulatory agency) identified 10 topics for a systematic literature search through a modified Delphi technique. In accordance with standardised EULAR operating procedures, recommendations were derived for the management of large vessel vasculitis. In the absence of evidence, recommendations were formulated on the basis of a consensus opinion. Results: Seven recommendations were made relating to the assessment, investigation and treatment of patients with large vessel vasculitis. The strength of recommendations was restricted by the low level of evidence and EULAR standardised operating procedures. Conclusions: On the basis of evidence and expert consensus, management recommendations for large vessel vasculitis have been formulated and are commended for use in everyday clinical practice.